Celibacy and Charism in 1 Cor 7:5–7 - Poirier, John C. (Harvard theological review, 1996)
The diversity among introductions to Paul is a tribute to the apostle's genius. There are two basic reasons for the diversity of opinion that exists today: First, internal incoherency—the difficulty of sorting Paul's thought into center and periphery (or event and context); and second, external incoherency—the gaps in our information about one of the most famous and interesting lives of all time. No consensus has emerged on the question of Paul's place in the world. We make this point not because this study will address the problem directly, but because we shall make inferences from one of the views in current circulation, namely that there is a basis to Paul's claim to Pharisaism (Phil 3:5). Attacking this view, some scholars have thought of him as a “would-be Pharisee” at best. We, nevertheless, think that the preponderance of evidence situates Paul in a universalist Jewish, probably Pharisaic, context. Paul believed that many of the law's prescriptions were still valid. As an illustration of Paul's belief in the continuing validity of the law, this essay attempts to show that 1 Cor 7:5–7 is best understood in the context of ritual purity concerns. These concerns include both the injunction for spouses to abstain from sexual activity for a time of prayer and Paul's defense of a celibate lifestyle within his own charismatic self-understanding.